2000
DOI: 10.1542/peds.106.6.1349
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Colic: Crying Time Reduction With a Whey Hydrolysate: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: An extensively hydrolyzed whey formula is effective in reducing the duration of crying in a primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 27 publications
(15 reference statements)
1
72
1
6
Order By: Relevance
“…Our findings show that infants fed with a partially hydrolysed formula, added with a mixture comprising 90% GOS and 10% FOS, had a significant decrease in colic episodes after 1 week of treatment compared to infants from the control group, confirming data of a previous observational study (Savino et al, 2003) and according to most of the diet studies on infantile colic (Lucassen et al, 1998(Lucassen et al, , 2000Garrison and Christakis, 2000). The difference in crying time was even more significant after 2 weeks of treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings show that infants fed with a partially hydrolysed formula, added with a mixture comprising 90% GOS and 10% FOS, had a significant decrease in colic episodes after 1 week of treatment compared to infants from the control group, confirming data of a previous observational study (Savino et al, 2003) and according to most of the diet studies on infantile colic (Lucassen et al, 1998(Lucassen et al, , 2000Garrison and Christakis, 2000). The difference in crying time was even more significant after 2 weeks of treatment.…”
Section: Discussionsupporting
confidence: 89%
“…allergy to cow's milk protein), but the strength of the relationship is not well defined (Hill and Hosking, 2000;Kalliomäki et al, 2001;Sicherer, 2003). Hypoallergenic formulas and mainly extensively hydrolysed formulas are effective in the treatment of infantile colic, indicating that dietary factors can play an important role (Lindberg, 1999;Jakobsson et al, 2000;Lucassen et al, 2000). However, considering the favourable clinical course of infantile colic, the wide range of manifestations, the day to day variability of crying time and the fact that many but not all the affected infants have symptoms related to cow's milk allergy, the majority of the studies on dietary interventions, particularly in formula-fed infants, concluded that further research is necessary (Lucassen et al, 1998;Garrison and Christakis, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Infantile colic is generally considered a benign and self-resolving condition, 2 yet it poses a burden on the affected families and may even trigger violent behavior toward the child. 3 Causal hypotheses relate to a gastrointestinal or a neurodevelopmental origin, such as altered gut microflora, 4,5 altered gastrointestinal motility, 6 lactose intolerance, 7,8 or a disorder in behavior regulation mechanisms. 1,9 Some consider infantile colic as an outlier in the developmental variation.…”
Section: Discussionmentioning
confidence: 99%
“…Они реко-мендованы, если колики не сочетаются с клинически-ми проявлениями атопического дерматита, и к тому же имеют преимущества перед глубокими гидролизатами в отношении цены. Эффективность указанных смесей при детских коликах подтверждена в рандомизирован-ных контролируемых исследованиях [17,18]. Более того, в ряде случаев эти смеси содержат пребиотики или отно-сятся к низколактозным смесям, что также способствует снижению частоты эпизодов колик в неделю.…”
Section: кишечные коликиunclassified